Incentivizing Schooling for Learning : Evidence on the Impact of Alternative Targeting Approaches - Barrera-Osorio, Felipe; Filmer, Deon (World Bank, Washington, DC, 2013)
This paper evaluates a primary school scholarship program in Cambodia with two different targeting mechanisms, one based on poverty level and the other on baseline test scores ("merit"). Both targeting mechanisms increased enrollment and attendance. However, only the merit-based targeting induced positive effects on test scores. The paper shows that the asymmetry of response is unlikely to have been driven by differences between recipients' characteristics. Higher student and family effort among beneficiaries of the merit-based scholarships suggest that the framing of the scholarship mattered for impact. The results suggest that in order to balance equity and efficiency, a two-step targeting approach might be preferable: first, target low-income individuals, and then, among them, target based on merit.